Pain and quality of life in patients undergoing radiotherapy for spinal metastatic disease treatment - Valesin Filho, Edgar S.; De Abreu, Luiz Carlos; Lima, Guilherme H.V.; De Cubero, Daniel I.G.; Ueno, Fabrício H.; Figueiredo, Gustavo S.L.; Valenti, Vitor E. [UNESP]; De Mello Monteiro, Carlos Bandeira; Wajnsztejn, Rubens; Fujiki, Edison N.; Neto, Modesto Rolim; Rodrigues, Luciano M. (Springer Nature, 2013)
Background: Radiotherapy is an important tool in the control of pain in patients with spinal metastatic disease. We aimed to evaluate pain and of quality of life of patients with spinal metastatic disease undergoing radiotherapy with supportive treatment. Methods. The study enrolled 30 patients. From January 2008 to January 2010, patients selection included those treated with a 20Gy tumour dose in five fractions. Patients completed the visual analogue scale for pain assessment and the SF-36 questionnaire for quality of life assessment. Results: The most frequent primary sites were breast, multiple myeloma, prostate and lymphoma. It was found that 14 spinal metastatic disease patients (46.66%) had restricted involvement of three or fewer vertebrae, while 16 patients (53.33%) had cases involving more than three vertebrae. The data from the visual analogue scale evaluation of pain showed that the average initial score was 5.7 points, the value 30days after the end of radiotherapy was 4.60 points and the average value 6months after treatment was 4.25 points. Notably, this final value was 25.43% lower than the value from the initial analysis. With regard to the quality of life evaluation, only the values for the functional capability and social aspects categories of the questionnaire showed significant improvement. Conclusion: Radiotherapy with supportive treatment appears to be an important tool for the treatment of pain in patients with spinal metastatic disease. © 2013 Valesin Filho et al; licensee BioMed Central Ltd.
Keywords: Neoplasm metastasis; Quality of life; Radiotherapy; dexamethasone; adult; aged; breast cancer; cancer pain; cancer radiotherapy; clinical article; female; human; lymphoma; male; multiple myeloma; prostate cancer; quality of life; radiation dose; Short Form 36; social aspect; spinal metastatic disease; spine metastasis; visual analog scale